Análisis De Tipologías De Construcciones Alternativas Aplicadas A La Construcción De Un Centro Cultural Riobamba-Ecuador - Carlos Renato Chávez Velásquez; Francisco Cepeda Yautibug; Luis Enrique Ávila Granda; Wilian Ernesto Balseca del Valle; Juan Enrique Ureña Moreno; Sofía Andrea Basantes Vinueza (European Scientific Journal, ESJ, 2017)
The traditional construction on land in the Ecuadorian highlands has been displaced by new construction methodologies and materials. The present study shows in detail the most used vernacular materials, describing their potential and comparing them accurately to the contemporary traditional solid brick. The modeling’s of each of the materials were executed/built/created in a small area of the Cultural Center of the Polytechnic School of Chimborazo. This was possible to do by using specialized software that details the thermal behavior and by knowing in advance the variations of temperature throughout the day and night in the Ecuadorian highlands. The Cultural Center is a center that opens a space for the exchange of intercultural knowledge and aims to teach the importance of sustainability by using and optimizing resources. This research aims to present the alternative of building thermal comfort buildings with sustainable materials within the university campus. These building will represent a space for teaching and learning among students, teachers and visitors who wish to learn about Cultural Heritage, Natural Resources, Sustainability, etc. Finally, this research contributes to the higher education system in the university as it goes alone with the teaching objectives established in each School, especially in the school of Ecotourism.